Woman at Grange meeting - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a woman sitting next to a man at a Grange meeting. She is wearing a sash that reads "California State [Grange]." There is a small bouquet of flowers on the table in front of her.